Ekonomicheskaia programma . Ekonomicheskaia programma . Economic Program . Экономическая программа - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. The Commonwealth of Independent States (CIS) heads of states discuss the possibility of creating a unified information and economic space. Featured in the program: Akaev, Askar Akaevich (President of Kyrgyzstan); Yeltsin, Boris Nikolayevich (President of the Russian Federation); IAkovlev, Egor (President of the TV "Ostankino"); Kravchuk, Leonid Makarovich (President of Ukraine); Dzhugeli, Vissarion (Minister of Industry of Georgia) Главы государств обсуждают возможности создания единого информационного и экономического пространства. В программе участвуют: Акаев, Аскар Акаевич (Президент Киргизии); Ельцин, Борис Николаевич (Президент Российской Федерации); Яковлев, Егор (Президент телекомпании "Останкино"); Кравчук, Леонид Макарович (Президент Украины); Джугели, Виссарион (Министр промышленности Грузии)